Integrating Voice Quality Cues in the Pitch Perception of Speech and Non-speech Utterances - Kuang, Jianjing; Liberman, Mark (Frontiers in Psychology, 2018)
Pitch perception plays a crucial role in speech processing. Since F0 is highly ambiguous and variable in the speech signal, effective pitch-range perception is important in perceiving the intended linguistic pitch targets. This study argues that the effectiveness of pitch-range perception can be achieved by taking advantage of other signal-internal information that co-varies with F0, such as voice quality cues. This study provides direct perceptual evidence that voice quality cues as an indicator of pitch ranges can effectively affect the pitch-height perception. A series of forced-choice pitch classification experiments with four spectral conditions were conducted to investigate the degree to which manipulating spectral slope affects pitch-height perception. Both non-speech and speech stimuli were investigated. The results suggest that the pitch classification function is significantly shifted under different spectral conditions. Listeners generally hear a higher pitch when the spectrum has higher high-frequency energy (i.e., tenser phonation). The direction of the shift is consistent with the correlation between voice quality and pitch range. Moreover, cue integration is affected by the speech mode, where listeners are more sensitive to relative difference within an utterance when hearing speech stimuli. This study generally supports the hypothesis that voice quality is an important enhancement cue for pitch range.